Application of communication technology in Malaysian public service - Mohd. Supa'at, Abu Sahmah (Penerbit UTM, 2008)
The Government of Malaysia is committed towards modernizing its administrative machinery and enhancing its service delivery mechanisms. The process of ensuring an efficient and effective public sector is being driven by the enabling capabilities of information and communications technology (ICT). The resultant widespread adoption of ICT systems by the public sector has meant that more and more Government agencies are moving towards the paperless work environment where ICT systems have become indispensable for the provision of Government services to citizens. The expansion of ICT systems within the public sector has in turn led to a significant increase in the number of public sector information repositories and other ICT-based installations and assets. The security of these ICT installations and assets are exposed to the vulnerability of open and networked electronic systems. As such agencies now face the additional responsibility of securing ICT-based Government information and systems as well as ensuring that they are available to authorized users. Communications Technology has proven its role in accelerating sustainable development and bridging the evergrowing divide in our present day society. There is however, a critical need to channel the vast potential of ICT in the right direction for the betterment of society and effective human development Asian economies are growing at a phenomenal rate. However, the rate of growth varies vastly among the different countries in Asia, thus creating a digital divide among nations. It is, therefore, imperative that Asian countries work together to harness the potential of ICT for development and ensure the divide is not a permanent chasm that marginalizes and excludes the less developed nations from the interconnected digital economy Some of our nations have acquired a high degree of competence in the applications of ICT and are leading in the field of software and hardware development. Thus, initiatives in sharing their experiences and best practices will facilitate other countries to learn from their knowledge and leapfrog in the race of human development. However, it must be noted that developing countries have specific issues and needs that have to be carefully examined. In view of this, the identification, selection and customization of the choice of technology have to be undertaken seriously and with a great degree of planning. Communication technologies are usually defined as technologies that facilitate communication and the processing and transmission of information by electronic means. This broad definition encompasses the full range of ICTs from radio and television to telephones (fixed and mobile), computers and the Internet. The revolutionary potential of ICTs lies in their capacity to instantaneously connect vast networks of individuals and organizations across great geographic distances at very little cost. As such, ICTs have been key enablers of development, facilitating flows of information, capital, ideas, people and products. An explicit focus on using ICTs in pursuit of development goals allows countries to achieve a wide diffusion of benefits from ICTs and contributes to both broad-based economic growth and specific development goals. Moreover, a holistic approach that sees ICTs as key development enablers recognizes that the potential of ICTs is linked to a complex mixture of international, national and local conditions. A number of interrelated factors should be addressed to maximize the benefits of ICTs for development. These include deploying ICT infrastructure, building human capacity, establishing a transparent and inclusive policy process, creating incentives for enterprise, and developing appropriate content. For all these to be realized, there is a need to understand the critical relationships between various strategic interventions in the context of local conditions and to secure the participation and commitment of all key stakeholders—local communities, non-governmental organizations (NGOs), governments and the private sector.